Implementasi Pertimbangan Hakim dalam Mengabulkan Permohonan Penetapan Wali Adhal Untuk Melaksanakan Perkawinan Menurut Hukum Islam (Studi Putusan Nomor 0055/ Pdt. P/ 2019/PA.Mt) - Baharudin Baharudin (Wajah Hukum, 2020)
Marriage must meet the requirements and harmony, one pillar that must be met is the marriage guardian. The existence of a guardian in a marriage contract is a must and is not a legal marriage agreement that is not carried out by the guardian. The guardian is placed as a pillar in marriage according to the agreement of scholars in principle. The problem in this research is how is the formal law in the stipulation of Metro Religious Court Number 0055 / Pdt P / 2019 / PA.Mt regarding the application of guardian application? and what is the basis for the judge's judgment (material law) in deciding on the Establishment of the Metro Religious Court Number 0055 / Pdt P / 2019 / PA.Mt regarding the application of a guardian?. The research method uses a normative and empirical juridical approach. The type of data used is secondary data and primary data. Collecting data through library research and field research. Analysis of the data used is qualitative juridical.